Identification of leaf rust resistance genes in selected Argentinean bread wheat cultivars by gene postulation and molecular markers - Vanzetti, Leonardo Sebastian; Campos, Pablo Eduardo; Demichelis, Melina; Lombardo, Lucio; Aurelia, Paola Romina; Vaschetto, Luis María; Bainotti, Carlos Tomas; Helguera, Marcelo (Pontificia Universidad Católica de Valparaíso, 2019)
Leaf rust, caused by Puccinia triticina Eriks. is a common and widespread disease of bread wheat (Triticum aestivum L.), in Argentina. Host resistance is the most economical, effective and ecologically sustainable method of controlling the disease. Gene postulation helps to determine leaf rust resistance genes (Lr genes) that may be present in a large group of wheat germplasm. Additionally presence of Lr genes can be determined using associated molecular markers. The objective of this study was to identify Lr genes that condition leaf rust resistance in 66 wheat cultivars from Argentina. Twenty four differential lines with individual known leaf rust resistance genes were tested with 17 different pathotypes of leaf rust collected from Argentina. Leaf rust infection types produced on seedling plants of the 66 local cultivars were compared with the infection types produced by the same pathotypes on Lr differentials to postulate which seedling leaf rust genes were present. Presence of Lr9, Lr10, Lr19, Lr20, Lr21, Lr24, Lr25, Lr26, Lr29, Lr34, Lr35, Lr37, Lr47 and Lr51 was also determined using molecular markers. Eleven different Lr genes were postulated in the material: Lr1, Lr3a, Lr3ka, Lr9, Lr10, Lr16, Lr17, Lr19, Lr24, Lr26, Lr41. Presence of Lr21, Lr25, Lr29, and Lr47 could not be determined with the seventeen pathotypes used in the study because all were avirulent to these genes. Eleven cultivars (16.7%) were resistant to all pathotypes used in the study and the remaining 55 (83.3%) showed virulent reaction against one or more local pathotypes. Cultivars with seedling resistance gene combinations including Lr16 or single genes Lr47 (detected with molecular marker), Lr19 and Lr41, showed high levels of resistance against all pathotypes or most of them. On the opposite side, cultivars with seedling resistance genes Lr1, Lr3a, Lr3a + Lr24, Lr10, Lr3a + Lr10, Lr3a + Lr10 + Lr24 showed the highest number of virulent reactions against local pathotypes. Occurrence of adult plant resistance genes Lr34, Lr35 and Lr37 in local germplasm was evaluated using specific molecular markers confirming presence of Lr34 and Lr37. Our data suggest that combinations including seedling resistance genes like Lr16, Lr47, Lr19, Lr41, Lr21, Lr25 and Lr29, with adult plant resistance genes like Lr34, SV2, Lr46 will probably provide durable and effective resistance to leaf rust in the region.